Cerâmicas refratárias macroporosas derivadas de espumas ultraestáveis estabilizadas com partículas cerâmicas - Santos Junior, Tiago dos (2020)
Innovation on materials for heat conservation in high-temperature industrial processes is seen as an important strategy for Energy Efficiency. Fundamental studies can support the development of these materials and the adoption of processing routes resulting in lower environmental impact should be considered to produce them. This thesis presents the development of Al2O3-based refractory macroporous ceramics prepared by direct foaming with the help of mechanoquantum simulations. Liquid foams stabilised with Al2O3 particles were developed after partial hydrophobisation of their surfaces with nontoxic amino acids. These foams attained extended lifetime and were stable for more than 100 hours. To produce solid samples derived from them, a binder based on calcium aluminate cement was developed based on mechano-quantum simulations. This binder is comprised of an aqueous suspension of calcium aluminate particles stabilised by gluconate, a non-toxic molecule. The hydration reactions of calcium aluminates were reactivated with a weak organic acid and allowed the production of solid samples with elevated porosity (≥ 70%) and cold crushing strength reaching 30 MPa after thermal treatment. Also, the in situ formation of a phase with lower volumetric density was studied to counteract the volumetric shrinkage of solid samples after firing. Calcium carbonate was used and, after processing at 1600°C for 5 hours, calcium hexaluminate (CA6) was identified. The formation of this phase helped to reduce the linear shrinkage from values close to 19% down to 4% maintaining the total porosity above 80%. The results presented in this thesis pointed out that the combination of computational techniques on quantum level and experimental routes can favour the development of new materials and advanced technologies combining superior performance and a higher commitment to the environment.